Superiority of ivermectin 1% cream over metronidazole 0·75% cream in treating inflammatory lesions of rosacea: a randomized, investigator‐blinded trial. (11th February 2015) - Taieb, A.; Ortonne, J.P.; Ruzicka, T.; Roszkiewicz, J.; Berth‐Jones, J.; Peirone, M.H.; Jacovella, J.; the Ivermectin Phase III study group
Summary Background Few therapeutic alternatives currently exist in the treatment of papulopustular rosacea (PPR). Objectives To demonstrate superiority of once‐daily ivermectin 1% cream (IVM 1%) once daily vs. twice‐daily metronidazole (MTZ 0·75%) cream, regarding percentage reduction of inflammatory lesions in subjects with moderate to severe PPR. Methods In this Phase 3, investigator‐blinded, randomized, parallel‐group study, subjects received IVM 1% once daily, or MTZ 0·75% twice daily over 16 weeks. Efficacy assessments were inflammatory lesion counts and Investigator's Global Assessment (IGA). Safety assessments included incidence of adverse events (AEs) and local tolerance parameters. Subjects evaluated their disease following a 5‐grade scale and completed questionnaires. Results A total of 962 subjects were randomized to receive IVM 1% (n = 478) or MTZ 0·75% (n = 484). At week 16, IVM 1% was significantly superior to MTZ 0·75% in terms of reduction from baseline in inflammatory lesions (83·0% vs. 73·7%; P < 0.001), observed as early as week 3 (Last Observation Carried Forward, LOCF). IGA results (subjects 'clear' or 'almost clear') also favoured IVM 1%: 84·9% vs. 75·4%, respectively (P < 0.001). Incidence of AEs was comparable between groups and local tolerability was better for IVM 1%. More subjects receiving IVM rated their global improvement as 'excellent' or 'good.' Conclusions Ivermectin 1% cream was significantly superior to MTZ 0·75% cream and achieved high patient satisfaction.